PERTEMPURAN DI SELAT BALI PADA MASA REVOLUSI FISIK 1945-1950 - Pidada Ida Bagus Astika (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2020)
The Balinese got acquainted with the Dutch for the first time through Cornellis de Houtman, followed by Cornellis Heemskerck. This introduction expresses friendship with the king Dalem Dalem Bekung at the Gelgel palace and continues to ask for permission to trade. It turned out that he got approval from the king Dalem Bekung. This atmosphere changed in the 19th century where the Dutch wanted to dominate Bali so that there was resistance from the kings in Bali such as: the Buleleng War, Jagaraga War, Kusamba War, Banjar War, Puputan Badung War and finally Puputan Klungkung War. This resistance continued under the leadership of I Gusti Ngurah Rai. To strengthen his troops, the way to do this was to seize weapons from the Japanese hands, by storming their forces throughout Bali on December 13th, 1945. This attack was a failure because it had been known in advance by the Japanese army. Then I Gusti Ngurah Rai and his friends went to Java to ask for weapons and report the situation in Bali to the leaders in Java. On April 3rd, 1946 I Gusti Ngurah Rai and his friends returned to Bali. During this trip there was a battle in the Bali Strait which caused the death of Cokorda Rai Gambir and Cokorda Dharma Putra, while Cokorda Oka Sudarsana and 2 (two) men who were supported were taken to Gilimanuk. The journey continued by I Gusti Ngurah Rai on April 4th, 1946 where landed at Yeh Kuning. In order for the struggle to continue the leaders sought weapons by making their own and carrying out attacks on NICA posts in Bali. Although the warriors' possessions are limited, they last long enough.